Most prominent challenges in translational neuroscience and strategic solutions to bridge the gaps: Perspectives from an editorial board interrogation - Dirk M. Hermann; Marco Bacigaluppi; Claudio L. Bassetti; Gabrio Bassotti; Johannes Boltze; Andrew Chan; Turgay Dalkara; Adam Denes; Exuperio Diez-Tejedor; Richard Dodel; Thorsten R. Doeppner; Egor Dzyubenko; et al. (Exploration of Neuroscience)
Recent progress in translational neuroscience has significantly advanced our understanding of neurological diseases. Research progress closely went in line with innovations in research methods, which have expanded our insights considerably beyond previous limits. However, despite the development of disease-modifying treatments, therapeutic options in brain diseases still lag behind fundamental discoveries in basic neuroscience. This perspective examines the factors that hinder clinical progress in translational neuroscience and provides solutions on how to overcome them. Editorial board members of Exploration of Neuroscience were interrogated about the most prominent challenges they see in translational neuroscience and about possible ways to overcome these issues. Key challenges were seen at the interface between experimental research and clinical studies by several members, both from the basic and applied neuroscience fields, which include the selection of appropriate study readouts and endpoints. The establishment of refined study endpoints, combined with biomarkers capable of predicting treatment responses in human patients, will be crucial for the successful clinical implementation of new therapies. Further obstacles were found in the standardization of experimental models, interventions, and assessments both in animals and humans, as well as in the development of personalized treatment strategies. These challenges can be addressed through more clearly defined experimental procedures that closely match clinical conditions and precision-based approaches that ensure efficient therapeutic responses. As a great opportunity, treatment options targeting pathophysiological processes in multiple brain diseases and disease processes in different organ systems were noted. Significant barriers remain in the funding of investigator-driven clinical trials through public research programs, as well as the education of translational and clinician scientists dedicated to clinical translation. Enhanced communication between experimental neuroscientists and clinicians, with a shared understanding and common language, will be essential for the success of future research endeavors.